Towards enhancing local citizen participation in Uganda - David Mwesigwa (Dynamics of Politics and Democracy, 2021)
Purpose: The purpose of this paper is to propose an alternative model of enhancing citizen participation in Uganda. Research Methodology: The central approach for this paper was review of obtainable theoretical and conceptual writings on citizen participation in Uganda and other parts of the world. Literature review is the gathering of information from obtainable resources such as educational journals and statistical periodicals. The approach has been demonstrated to be very effective and can be applied at any stage of a research process. Results: Citizen Participation encourages marginalised groups to be organised in structures under their control; brings knowledge of their social environment and process to the local government agenda in a way that no other structure can as well as fostering self-reliance. Limitations: This study took a desk research and the actual opinions from selected citizens may be parallel to the conclusions obtained in this review. Contribution: The study can be used for local government managers implementing community-driven projects. Keywords: Citizen participation, policy implementation, stakeholders, bureaucrats, local leaders